Coating of manganese functional polyetheretherketone implants for osseous interface integration - Yang, Xin; Xiong, Shouliang; Zhou, Jing; Zhang, Yinchang; He, Huazheng; Chen, Pingbo; Li, Congming; Wang, Qiang; Shao, Zhiqiang; Wang, Lei (Frontiers in Bioengineering and Biotechnology, 2023)
Polyetheretherketone (PEEK) has been used extensively in biomedical engineering and it is highly desirable for PEEK implant to possess the ability to promote cell growth and significant osteogenic properties and consequently stimulate bone regeneration. In this study, a manganese modified PEEK implant (PEEK-PDA-Mn) was fabricated via polydopamine chemical treatment. The results showed that manganese was successfully immobilized on PEEK surface, and the surface roughness and hydrophilicity significantly improved after surface modification. Cell experiments in vitro demonstrated that the PEEK-PDA-Mn possesses superior cytocompatibility in cell adhesion and spread. Moreover, the osteogenic properties of PEEK-PDA-Mn were proved by the increased expression of osteogenic genes, alkaline phosphatase (ALP), and mineralization in vitro. Further rat femoral condyle defect model was utilized to assess bone formation ability of different PEEK implants in vivo. The results revealed that the PEEK-PDA-Mn group promoted bone tissue regeneration in defect area. Taken together, the simple immersing method can modify the surface of PEEK, giving outstanding biocompatibility and enhanced bone tissue regeneration ability to the modified PEEK, which could be applied as an orthopedic implant in clinical.